To determine which equation creates a true equivalent system, we first need to look at the existing equations in the systems provided.
The equations for both systems are:
System A:
- \( -x + y = 1 \)
- \( x + y = 11 \)
System B:
- \( x + y = 11 \) (repeated, so it doesn't provide new information)
To identify an equivalent system, we can manipulate one of the existing equations. An equation is equivalent if it represents the same line or value on a graph.
Checking the Options
-
\(-2x - 2y = -22\): If we divide this equation by -2, we would get \(x + y = 11\), which is equivalent to one of the equations in System B.
-
\(2y = 12\): If you solve for \(y\), you get \(y = 6\). This does not create an equivalent system as it doesn't relate to the original equations effectively.
-
\(-x - y = -1\): If we rearrange this equation, we can adjust it to \(x + y = 1\), which is not equivalent to \(x + y = 11\).
-
\(2x + 2y = 12\): If we divide this equation by 2, we arrive at the equation \(x + y = 6\), which is also not equivalent to the equations in the original systems.
Conclusion
The only equation that forms a true equivalent system is:
\(-2x - 2y = -22\)
This represents the same relationship as \(x + y = 11\) and thus creates a valid equivalent system.